Set equation equal to 0:
(3x + 12) - (5x - 6) = 0
Combine terms:
3x - 5x + 12 + 6 = 0
Add/subtract terms:
-2x + 18 = 0
Subtract 18 from both sides:
-2x = -18
Divide both sides by -2:
x = 9
2007-02-13 16:01:37
·
answer #1
·
answered by Joy M 7
·
1⤊
1⤋
re write to this:
3x + 12 - 5x + 6 = 0 <--- applied minus sign to the 5x-6 bracket, making the positive 5 a - and the -6 a positive. sign inversion
-2x + 18 = 0 <--- Combine like terms
-2x = 0 - 18 <- seperate x from the numbers
-2x = -18
x = 9 <---- divide by -2
2007-02-13 16:02:46
·
answer #2
·
answered by indieforcutie 3
·
0⤊
0⤋
The minus sign means you'll have to change the signs found inside the following parentheses.
3x + 12 - 5x + 6 = -2x + 18
2007-02-13 16:03:40
·
answer #3
·
answered by ecolink 7
·
1⤊
0⤋
(3x+12)-(5x-6) distribute the "-"
3x+12-5x+6 combine like terms
-2x+18
2007-02-13 16:01:57
·
answer #4
·
answered by yupchagee 7
·
0⤊
0⤋
3x + 12-5x + 6
-2x+18=0
-2x= -18
x= -18/-2
x= 9
2007-02-13 16:03:03
·
answer #5
·
answered by purpleskies 1
·
0⤊
0⤋
3x-5x + 12-(-6) = -2x + 18
-2(x-9)
2007-02-13 16:02:34
·
answer #6
·
answered by kellenraid 6
·
0⤊
0⤋
use like terms.. 3x-5x is gonna give u -2x....12 minus negatuve 6 is 18...soo -2x+18
2007-02-13 16:00:26
·
answer #7
·
answered by luhb u much!! 4
·
0⤊
0⤋
=(3X+12)-(5X-6)
=3x+12-5X+6
=-2X+18
2007-02-13 16:27:59
·
answer #8
·
answered by Archu 2
·
0⤊
0⤋
3x+12 * -5x+6=0
3x=-12 or 5x=-6
x=-4 or -6/5
2007-02-13 16:02:21
·
answer #9
·
answered by Anonymous
·
0⤊
1⤋
Nothing to solve but reducing to lowest form: 6-2x
2007-02-13 16:08:25
·
answer #10
·
answered by Don R 5
·
0⤊
1⤋